Эволюция клинкового оружия средневековых кочевников в степях Южной Украины и Крыма до вторжения монголо-татар - Сейдалиев, Э.И. (Боспорские исследования, 2009)
Evolution of blade weapon of medieval nomads in the steppes of the south of Ukraine and the Crimea before Mongol horde period has been observed. Changes of weapon of the Khazars, Pechengs and Polovets have been researched. Some theories devoted to the topic are given and critically analyzed. A number of sources on the history of nomads’ military science have been covered. The aim of the article was to follow the evolution of blade weapon not only as an individual item of arms of medieval nomads and to show how military equipment were changing according to social, political and cultural processes.